Mixing in the NETmix Reactor - Matos, Joana; Santos, Ricardo J.; Dias, Madalena M.; Lopes, José Carlos B. (Frontiers in Chemical Engineering, 2021)
NETmix is a static mixing reactor composed of a network of mixing chambers interconnected by channels. The repetitive mixing pattern inside the reactor enables the use of reduced geometries to represent the NETmix network, such as the ExtendedNUB model, used in this work. Mixing in NETmix is based on the impingement of jets, issuing from channels. Inside the chambers, the jets are engulfed by dynamic vortices which can be quantified using Lagrangian techniques. Batch Lagrangian Mixing Simulation (BLMS) is based on successive injections of particles to measure the fraction of the fluids at the outlet of the mixing chambers. The distribution of the outlet fraction of particles indicates that it is possible to have nearly perfect mixing inside the NETmix chambers, depending on the dimensions of the channels and chambers. The NETmix design is here optimized in relation to the chamber diameter to channel width ratio, D/d. Results from BLMS show that best performance in NETmix occurs for 6.65≤D/d≤6.85.